Inhibitory effect of mixture herbs/ spices on formation of heterocyclic amines and mutagenic activity of grilled beef - Sepahpour, Shabnam; Selamat, Jinap; Khatib, Alfi; Abdul Manap, Mohd Yazid; Abdull Razis, Ahmad Faizal; Hajeb, Parvaneh (Taylor & Francis Group, 2018)
Natural antioxidants in spices and herbs have attracted considerable attention as potential inhibitors against the formation of mutagenic heterocyclic amines (HCAs) in heat-processed meat. In this study, the inhibitory activity of four spices/herbs and their mixtures on HCAs formation in grilled beef were examined. A simplex centroid mixture design with four components comprising turmeric, curry leaf, torch ginger and lemon grass in 19 different proportions were applied on beef samples before grilling at 240 ºC for 10 min. The HCAs were extracted from the samples using solid phase extraction (SPE) method and analysed using Liquid chromatography mass spectrometry LC-MS/MS. All spices/herbs in single or mixture forms were found to reduce total HCA concentrations in marinated grilled beef ranging from 21.2% for beef marinated with curry leaf to 94.7% for the combination of turmeric and lemon grass (50:50 w/w). At the optimum marinade formula (turmeric: lemon grass 52.4%: 47.6%), concentration of 2-amino-3-methylimidazo[4,5-f]quinolone (IQ), 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), Harman, Norharman and AαC were 2.2, 1.4, 0.5, 2.8 and 1.2 ng/g, respectively. The results of the mutagenic activity demonstrated that this optimised marinade formula significantly (p < 0.05) diminished mutagenicity of marinated grilled beef in bacterial Ames test.